Teaching The Analysis Of Cho’lpon’s Poetry - Omanova Mubora Abdurazakovna (Genius Journals, 2025)
The education system has also undergone changes, adapting to the updated principles of pedagogical thinking. In our country, serious attention was paid to the formation of an independent, educated, creative and imaginative personality, increasing his spirituality, ensuring his intellectual and spiritual maturity. After all, only inquisitive, creative, enterprising, noble personalities can develop the state and society.
Keywords: Literary; educational; pedagogical